Disclosing the Antioxidant and Neuroprotective Activity of an Anthocyanin-Rich Extract from Sweet Cherry (Prunus avium L.) Using In Vitro and In Vivo Models - Monica Filaferro; Alessandro Codeluppi; Virginia Brighenti; Francesca Cimurri; Ana María González-Paramás; Celestino Santos-Buelga; Davide Bertelli; Federica Pellati; Giovanni Vitale (MDPI AG, 2022)
In this study, an autochthonous variety of sweet cherry (Prunus avium L.), namely "Moretta di Vignola", was processed to prepare extracts rich in polyphenols, which were characterized by high-performance liquid chromatography (HPLC) separation coupled to UV/DAD and ESI-MSn analysis. Then, a sweet cherry anthocyanin-rich extract (ACE) was prepared, fully characterized and tested for its activity against Parkinson's disease (PD) in cellular (BV2 microglia and SH-SY5Y neuroblastoma) and in Drosophila melanogaster rotenone (ROT)-induced model. The extract was also evaluated for its antioxidant activity on Caenorhabditis elegans by assessing nematode resistance to thermal stress. In both cell lines, ACE reduced ROT-induced cell death and it decreased, alone, cellular reactive oxygen species (ROS) content while reinstating control-like ROS values after ROT-induced ROS rise, albeit at different concentrations of both compounds. Moreover, ACE mitigated SH-SY5Y cell cytotoxicity in a non-contact co-culture assay with cell-free supernatants from ROT-treated BV-2 cells. ACE, at 50 µg/mL, ameliorated ROT (250 μM)-provoked spontaneous (24 h duration) and induced (after 3 and 7 days) locomotor activity impairment in D. melanogaster and it also increased survival and counteracted the decrease in fly lifespan registered after exposure to the ROT. Moreover, heads from flies treated with ACE showed a non-significant decrease in ROS levels, while those exposed to ROT markedly increased ROS levels if compared to controls. ACE + ROT significantly placed the ROS content to intermediate values between those of controls and ROT alone. Finally, ACE at 25 µg/mL produced a significant increase in the survival rate of nematodes submitted to thermal stress (35 °C, 6-8 h), at the 2nd and 9th day of adulthood. All in all, ACE from Moretta cherries can be an attractive candidate to formulate a nutraceutical product to be used for the prevention of oxidative stress-induced disorders and related neurodegenerative diseases.